The role of psychic distance stimuli on the East-West FDI location structure in the EU: Evidence from Spanish MNEs - Alfredo Jiménez Palmero; Juan José Durán Herrera; Juan Manuel de la Fuente Sabaté (Journal for East European Management Studies, 2013)
Eastern Europe nowadays represents an important and attractive economic area for foreign direct investment. Determinants of investments have converged with those of other European countries. However, it has been argued that a differentiated East-West structure still exists in Europe. This study examines the existence of such a structure from the novel perspective of psychic distance stimuli, showing no evidence of its persistence. Moreover, the results provide evidence on the fundamental role played by different dimensions of psychic distance, especially in levels of industrial development and language, as obstacles to foreign direct investments. On the contrary, distance in education is positively associated with investments, reflecting an efficiency-seeking MNE approach. – – Heutzutage ist Osteuropa ein wichtiger und attraktiver Wirtschaftsraum für ausländische Direktinvestitionen. Die Determinanten der Investitionen haben sich denen anderer europäischer Länder angenähert. Allerdings wurde angeführt, dass in Europa noch immer eine differenzierte Ost-West-Struktur vorhanden ist. Die vorliegende Studie untersucht die Existenz einer solchen Struktur aus der neuartigen Perspektive der psychischen Distanz-Stimuli, die keine Anzeichen für Beharrlichkeit zeigen. Darüber hinaus liefern die Ergebnisse Hinweise auf die fundamentale Rolle, welche die verschiedenen Dimensionen der psychischen Distanz spielen, vor allem in den Stufen der industriellen Entwicklung und der Sprache, als Hindernis für ausländische Direktinvestitionen. Die Kluft in der Bildung ist positiv mit Investitionen verbunden, was auf einen Effizienz-orientierten Ansatz schließen lässt.
Keywords: 650; psychic distance; multinational enterprise; direct foreign investment; conditional logit model; Central and Eastern European countries; Auslandsinvestition; Spanisch; Wirtschaftspsychologie; Osteuropa